2022
DOI: 10.1111/are.16052
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐species probiotics enhance growth of Nile tilapia ( Oreochromis niloticus ) through upgrading gut, liver and muscle health

Abstract: Aquaculture is broadly recognized among the most competitive and promising sectors for providing income and nutritional security to humanity, as demand for animal protein from fish is growing globally (Mohapatra et al., 2012). Although the sector has achieved remarkable improvement, in recent times, the income of this field is declining because of huge feed costs that typically account for over 70% of total production expenses Hossain, Rahman, et al., 2020;Nguyen et al., 2020). Moreover, the optimization of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Similar results were observed by Abdel-Tawwab et al [72] in Nile tilapia (O. niloticus), Sharma et al [73] in mrigal (Cirrhinus cirrhosis), and Talpur and Ikhwanuddin [74] in Asian seabass (Lates calcarifer) when diets containing S. cerevisiae and probiotics were used. Consistent with the findings of the current study, Hossain et al [75,76] noted that blood glucose levels did not significantly change after administering multispecies probiotics, indicating that fish raised with such probiotics remained in good health.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were observed by Abdel-Tawwab et al [72] in Nile tilapia (O. niloticus), Sharma et al [73] in mrigal (Cirrhinus cirrhosis), and Talpur and Ikhwanuddin [74] in Asian seabass (Lates calcarifer) when diets containing S. cerevisiae and probiotics were used. Consistent with the findings of the current study, Hossain et al [75,76] noted that blood glucose levels did not significantly change after administering multispecies probiotics, indicating that fish raised with such probiotics remained in good health.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present study showed that the LAB and TVC in the gut of H. fossilis increased significantly when laboratory-developed multispecies probiotics were used in the biofloc system. Previous research has suggested that probiotics can modify the structure and rate of cellular renewal in fish intestines, leading to improvements in histo-morphometric properties [75,76,81,82]. In this study, the use of laboratory-developed multispecies probiotics had a notable impact on intestinal morphology; it resulted in enhanced wall thickness, muscle layer, length, area, and width of the gut villus, as well as increased mucosal fold development and certain immune responses.…”
Section: Discussionmentioning
confidence: 68%
“…Likewise this study, numerous scientific literatures documented that the inoculation of beneficial bacteria either in water or in feed stimulated growth performance, nutrient digestibility (indicated by low FCR) and survival for different fishes and shrimps such as, Bacillus subtilis increased weight gain and feed utilization for grouper ( Epinephelus coioides ) in 28 day culture ( Liu et al, 2017 ); incorporation of B. cereus and B. thuringiensis enhanced final weight and feed conversion efficiency in Asian seabass, Lates calcarifer ( Ghanei-Motlagh et al, 2021 ); mixture of Bacillus spp., and Lactobacillus spp. improved weight gain and SGR in Nile tilapia ( Oreochromis niloticus ), and carp ( Cirrhinus cirrhosus ) ( Apún-Molina et al, 2009 , Hossain et al, 2022a , Hossain et al, 2022b , Ramos et al, 2017 ); B. coagulans and Rhodpseudomonas palustris together resulted better growth performance and low FCR for Nile tilapia ( Zhou et al, 2010 ); Bacillus sp., Vibrio sp., and Lactobacillus plantarum increased survival along with improved weigh gain and SGR in freshwater shrimp ( Macrobrachium rosenbergii ) ( Mujeeb Rahiman et al, 2010 ); Lactobacillus acidophilus supplement positively reflected in growth and FCR for African catfish, Clarias gariepinus ( Al-Dohail et al, 2011 ); usage of dietary probiotic mixture of B. subtilis , B. megaterium , and B. licheniformis increased the net production, feed conversion, survivability of channel catfish ( Ictalurus punctata ) ( Queiroz and Boyd, 1998 ); yeast ( Saccharomyces cerevisiae ) and Acinobacter ensured better growth and feed utilization in striped catfish, Pangasianodon hypophthalmus and Bighead catfish, Clarias macrocephalus ; respectively ( Boonanuntanasarn et al, 2019 , Bunnoy et al, 2019 ). In general, feed conversion efficiency and wellbeing of fish are reliant on the enzymatic activity, nutrient digestibility and absorption, similarly, better digestion and nutrient assimilation results better performance in growth.…”
Section: Discussionmentioning
confidence: 99%
“…etc. Though any single strain of these bacteria brings productivity in culture, integration of two or more strains provide better performance ( Hossain et al, 2022b ). For example, the combination of Bacillus and Lactobacillus are extensively used in aquaculture since they provide multiple benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previously conducted experiments focused on the use of single or multi-strain Streptomyces -based probiotics and overlooked the aspects of using multi-species Streptomyces -based probiotics. Several recently published original articles indicated the importance of multi-species probiotics as an eco-friendly growth stimulator in aquaculture [ 145 , 146 ]. Thus, the use of Streptomyces in combination with other bacterial species could induce promising health benefits in aquaculture and requires further consideration.…”
Section: Future Prospectsmentioning
confidence: 99%